PENGARUH ENVIRONMENTAL, SOCIAL, GOVERNANCE, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Basic Materials, Consumer Cyclicals, dan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Azka Nabila; Darsono Darsono (Diponegoro Journal of Accounting, 2025)
This study aims to analyze and examine the influence of Environmental, Social, Governance (ESG), and financial performance on firm value in basic materials, consumer cyclicals, and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This research employs stakeholder theory and resource-based theory as theoretical foundations.The research sample was selected using purposive sampling method, yielding 218 observations. Data were obtained through companies' annual reports published on the official IDX website and Bloomberg database. This study uses quantitative methods with multiple linear regression analysis techniques using SPSS 27 software to analyze the relationship between independent variables (environmental, social, governance, profitability, liquidity, leverage, and firm size) and the dependent variable (firm value measured by Tobin's Q).The results show that profitability (ROA) and liquidity (CR) have a positive and significant effect on firm value. Meanwhile, Environmental, Social, Governance, leverage, and firm size variables do not have a significant effect on firm value.